Listening to Graduates of a K-12 Bilingual Program: Language Ideologies and Literacy Practices of Former Bilingual Students - Dworin, Joel (GIST – Education and Learning Research Journal, 2011)
This study investigated the language and literacy practices of five graduates of a Spanish-English K-12 dual language immersion program through semistructured interviews to understand the residual impact of thirteen years in a Spanish-English bilingual school program. Drawing from sociocultural theory, the interviews also sought to provide an understanding of the participants’ specific social networks and uses of Spanish and cultural affinities. Transcripts of the interviews, which were 1-2 hours in length, were analyzed primarily for content related to language use, social networks, and cultural affiliations. Coding by general themes that emerged was done first, and then patterns within and across interview transcripts were identified and analyzed. The basic research question guiding this interview study was: What can be learned about the Spanish-English bilingualism and biliteracy of former students who attended a 13-year bilingual school program? Three main findings were: 1) All of the former students reported being bilingual and biliterate in English and Spanish; 2) Two prominent language ideologies in the everyday uses of Spanish by the participants were identified. One language ideology may be described as a functional language ideology, where Spanish was used primarily to accomplish only specific, limited kinds of communication with others. The other language ideology was one where linguistic and cultural affinities with native Spanish speakers were a key part of the participants’ orientation and use of Spanish; and 3) The issue of who may be reaping the most benefits from the K-12 dual language immersion program arose through an analysis of the interviews, especially at the secondary levels, because of the relatively small numbers of Latina/o students that completed the program. The findings are significant because they indicate some of the strengths and limitations of K-12 bilingual programs in the U.S. Given that there has been very little research in this area, the study provides educators and researchers with important concerns in bilingual education program implementation, as well as areas for further research.